Isolation, molecular identification and biodegradation capacities of indigenous hydrocarbon-degrading bacteria from tarball at Terengganu beach, Malaysia - Nkem, Bruno Martins; Halimoon, Normala; Md. Yusoff, Fatimah; Wan Johari, Wan Lutfi; Zakaria, Mohamad Pauzi; Medipally, Srikanth Reddy; Kannan, Narayanan (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
In this study, we isolated four indigenous hydrocarbon-degrading bacteria from tarball found in Rhu Sepuluh beach, Terengganu, Malaysia. These bacteria were identified based on their physiological characteristic and 16S rRNA gene sequence analysis, and they showed 99% similarity with Pseudomonas stutzeri strain A1501, Pseudomonas balearica strain SP1402, Cellulosimicrobium cellulans DSM 43879 and Acinetobacter baumannii ATCC 19606 respectively. Their hydrocarbon-degrading capabilities were tested using diesel-oil as sole carbon source. Results analysed using GC-MS, showed diesel-oil alkanes were degraded an average 30.5%, 16.4%, 64.4% and 58.1% with medium optical density reaching 1.172, 1.503, 0.967 and 1.515 by Pseudomonas stutzeri, Pseudomonas balearica, Cellulosimicrobium cellulans and Acinetobacter baumannii respectively in minimal salt media at 32oC for 10 days. Individual diesel-oil alkanes were degraded between 19.7% - 49.2% (P. stutzeri), 2.5% to 27.5% (P. balearica), 10% - 95.4% (C. cellulans) and 0.2% - 95.9% (A. baumannii). All strains utilized diesel-oil for growth. The study suggests all strains are part of indigenous hydrocarbon-degrading bacteria in tarball with potential for bioremediation of oil-polluted marine environment.